The Implication of Communication Axioms within Various Perspectives of Methodology and Research - Basuki Agus Suparno (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
It is very clear that communication axioms implied to theories of communication. A good theory usually gives the implication to the research methodology directly or indirectly. Through communication axioms, we understand that these formulations are generated from the discursive practices of community within the communication field conducted by the scholars. Here it is to say that each theory that was generated can not be separated from the historical perspectives. By giving the key foundation of communication axioms, this paper was meant to trigger many attempts in exploring communication in detail and more comprehensively.